A Corpus-based Lexical Study of Agricultural Sciences in Open and Distance Learning Coursebooks. - Haruna, Hamisu Hamisu; Ahmad Tajuddin, Azza Jauhar; Sulaiman, Wid Zuriana (Pertanika Journal of Social Sciences & Humanities, 2025)
Lexical knowledge is extremely important for learning success, especially in Open and Distance Learning (ODL), where students use printed texts as their main source of learning information. Although studies have indicated a favourable correlation between vocabulary and academic achievement, especially in advanced subjects such as agricultural sciences, recent research has not yet adequately addressed the lexical challenges in agricultural ODL coursebooks. This study involved a corpus analysis of 1.4 million words from five agricultural sub-disciplines at the National Open University of Nigeria (NOUN). Nation's British National Corpus and Corpus of Contemporary American English (BNC/COCA) word lists and Coxhead's Academic Word List (AWL) were used to analyse the lexical coverage required for comprehension thresholds of 95% and 98%. The results show that ODL students require 8,000-9,000 word families for independent reading and that the supplementary lists comprise 1.91% of the required word families. The AWL coverage remained stable across all levels (9.42%-11.75%), indicating a homogeneous academic lexical profile. Limitations include the focus on a single subject area and the reliance on corpus analysis. The findings from this study allow for targeted vocabulary instruction that integrates subject-specific terms, a balanced approach to academic vocabulary acquisition, evidence-based curriculum design, and learner support initiatives. This study makes a valuable contribution by identifying the specific lexical needs of students, creating relevant and comprehensible course materials, and thereby improving the quality of agricultural education in ODL learning environments.